The biogeography of insects' length–dry mass relationships. Issue 5 (26th December 2013) - Martin, Charles A.; Proulx, Raphaël; Magnan, Pierre; Dytham, Calvin; Lobo, Jorge M.
Abstract Biomass measures are central to estimating secondary productivity and studying how resources are distributed within an ecosystem. Because directly measuring insect biomass is a lengthy process, many authors have resorted to empirical length–dry mass relationships. The objective of this study was to evaluate the relative importance of latitude, climate and physical habitat (aquatic vs. terrestrial) in explaining the variability in length–dry mass relationships among insect populations. A global meta‐analysis of the body length–dry mass power coefficients of 457 insect samples was conducted using mixed‐effects models. The length–dry mass power coefficients of insects were positively related to the absolute latitude of the study site and to habitat type; with insects captured in aquatic habitats being characterised by higher allometric coefficients than terrestrial ones. Neither the annualised climatic variables (temperature and precipitation) nor the metamorphosis type of insect taxa had a significant effect on the allometric coefficients. The findings may lead to a generalised body length–dry mass relationship for insects, accounting for both the phylogenetic relatedness and the environmental (biotic and abiotic) context of populations.